SPECIFICS OF ANTIHYPERTENSION THERAPY IN HYPERTENSIVES OF VARIOUS CARDIOVASCULAR RISK (BY THE REGISTRY OF CHRONIC NON-COMMUNICABLE DISEASES IN TYUMENSKAYA OBLAST) - A. Yu. Efanov; Yu. A. Vyalkina; Yu. A. Petrova; Z. M. Safiullina; O. V. Abaturova; S. V Shalaev (Кардиоваскулярная терапия и профилактика)
Aim. To assess the specifics of antihypertension therapy (AHT) in hypertensives of various cardiovascular risk, in the registry of chronic non-communicable diseases in Tyumenskaya oblast.Material and methods. A random sample studied, of 1704 patients with hypertension, inhabitants of Tyumenskaya oblast (region), ascribed to dispensary follow-up. Mean age 62±7,5 y.o. Of those 31,5% (n=537) males. The prevalence and efficacy of AHT assessed according to cardiovascular risk level. The significance was evaluated with the criteria χ2.Results. AHT was characterized by the growth of the frequency of treatment approaches with cardiovascular risk consideration. Regular treatment took 33,9% patients of low and moderate risk vs 41,3% of high and very high (p<0,01). In the male group such tendency also took place. Gender specifics of AHT was characterized by that in the groups of high and very high risk females took medications significantly more commonly than males — 46,6% vs 29,1% in high risk group (p<0,01) and 47,5% vs 30% in very high risk group (p<0,01). With the increase of the risk level, there was decline of treatment efficacy — from 95% in low risk group to 32,5% in very high risk group; 53,1% of the participants were taking monotherapy, 32,9% — two drugs, 14,0% — ≥3 drugs. With the increase of risk grade there is tendency to increase of combinational AHT, however with no significant increase of efficacy. Treatment efficacy in high and very high risk patients comparing to patients with low and moderate risk was significantly lower — 33,1% vs 69,7% (p<0,01), respectively. Statins intake among the high and very high risk patients was 10,6-11,0% males and 7,8% females (p<0,05).Conclusion. AHT in hypertensives in Tymenskaya oblast, under dispensary follow-up, is characterized by insufficient usage of combinational drugs. With the raise of cardiovascular risk there is tendency to higher rate of combinational AHT. However there is no significant increase in efficacy of treatment with the increase of medications number. A very low rate of statins intake is noted. The obtained specifics witness for the necessity to optimize AHT among the high and very high risk patients — inhabitants of Tyumenskya oblast.